Biosorption of effluent organic matter onto magnetic biochar composite: Behavior of fluorescent components and their binding properties. (August 2016) - Wei, Dong; Ngo, Huu Hao; Guo, Wenshan; Xu, Weiying; Zhang, Yongfang; Du, Bin; Wei, Qin
Graphical abstract: Highlights: MBC was successfully prepared, characterized and applied for treating EfOM. Fluorescent components of EfOM were identified by using EEM–PARAFAC. Fluorescence quenching order of EfOM onto MBC was obtained from 2D-COS. The majority of EfOM in terms of MW were removed with different degrees. Abstract: Effluent organic matter (EfOM) is of great concern as one of main sources of organic pollutants from biologically treated wastewater, which is harmful to the quality of receiving waters. In present study, magnetic biochar composite (MBC) was successfully prepared, characterizated and applied to EfOM treatment. The interaction between EfOM and MBC was explored by a combination of excitation–emission matrix (EEM), parallel factor analysis (PARAFAC), synchronous fluorescence, two-dimensional correlation spectroscopy (2D-COS), and molecular weight distribution. Result implied that two fluorescence components were derived from EEM–PARAFAC, and their relative fluorescence intensity scores expressed decreased trend. Moreover, fluorescence quenching of EfOM with increased MBC took place sequentially in the following order: protein-like fraction < fulvic-like and humic-like fractions. Molecular weight distribution suggested that MBC had different uptake ability to various size ranges of EfOM. The obtained results could provide a potential application of fluorescence spectroscopy for EfOM treatment assessment.